2010
DOI: 10.1177/0272431610384484
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity and Substance Use Among Mexican-Heritage Preadolescents

Abstract: This study examined interactive relationships among ethnic identity, gender, time in the US, and changes in substance use outcomes among a school-based sample of 1,731 Mexican-heritage preadolescents (ages 9–13). Residual change multilevel models adjusting for school clustering and using multiply imputed data assessed changes from beginning to end of fifth grade in use of alcohol, cigarettes, marijuana and inhalants, and four substance use antecedents. Effects of ethnic identity were conditional on time in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 56 publications
1
34
1
Order By: Relevance
“…Studies have found that a strong ethnic identity is protective against substance use (Brook et al, 2010; Love et al, 2006; Marsiglia et al, 2004). However, other studies have found opposite (Zamboanga et al, 2009) or inconsistent (Kulis et al, 2012) associations.…”
Section: Culturally-related Protective Factorsmentioning
confidence: 84%
“…Studies have found that a strong ethnic identity is protective against substance use (Brook et al, 2010; Love et al, 2006; Marsiglia et al, 2004). However, other studies have found opposite (Zamboanga et al, 2009) or inconsistent (Kulis et al, 2012) associations.…”
Section: Culturally-related Protective Factorsmentioning
confidence: 84%
“…In line with social identity theories, ethnic identity has been consistently linked to higher self-esteem in adolescents (Bracey, Bamaca, & Umaña-Taylor, 2004; Umaña-Taylor & Updegraff, 2007). This literature with pan-Latino samples also shows associations between ethnic identity and other developmental outcomes, including less substance use (Kulis, Marsiglia, Kopak, Olmsted, & Crossman, 2012), better mental health (Umaña-Taylor & Updegraff, 2007; Umaña-Taylor, 2004) and better academic functioning (Fuligni, Witkow, & García Coll, 2005; Schwartz, Zamboanga, & Hernandez Jarvis, 2007; Umaña-Taylor & Updegraff, 2007), which in some cases appear to be mediated partially by self-esteem (Umaña-Taylor & Updegraff, 2007). …”
Section: Ethnic Identity In Latino Adolescentsmentioning
confidence: 89%
“…For example, some evidence suggests that boys may be slower in developing their ethnic identities than girls (Umaña-Taylor, Gonzales-Backen, & Guimond, 2009). In addition, past studies have found unique predictors for the ethnic identity formation of boys relative to girls (Bracey et al, 2004; Umaña-Taylor & Guimond, 2012) and unique protective effects (e.g., against substance use) for boys that did not generalize to girls (Kulis et al, 2012). Beyond the greater social maturity shown by girls (Umaña-Taylor et al, 2009), these gender differences are thought to reflect the expectation that the transmission of culture (e.g., traditions, values) across generations is the responsibility of women, and that in preparing girls for this role, parents tend to socialize girls more than boys to cultural practices (Hughes et al, 2006; Kulis et al, 2012; Umaña-Taylor & Guimond, 2012; Updegraff, McHale, Whiteman, Thayer, & Crouter, 2006).…”
Section: Ethnic Identity In Latino Adolescentsmentioning
confidence: 99%
“…However, it is possible that gender differentiates how ethnic identity affirmation may affect coping through substance use. For instance, a study on Mexican-heritage youth found that ethnic identity protected against substance use for boys more than for girls (Kulis, Marsiglia, Kopak, Olmsted, & Crossman, 2012). Thus, feeling proud about being Mexican American may play a unique role for boys more than for girls when it comes to coping through substance use.…”
Section: Discussionmentioning
confidence: 99%